Improving Student Speaking Skill Throught Collaborative Learning Strategy At Smpit Ummi Abiyyi Serang Baru - Andini, Sri; Eindo, Yon A.; Solo, Lenny (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Improving Student Speaking Skill Throught Collaborative Learning Strategy At Smpit Ummi Abiyyi Serang Baru Thesis. Bekasi : Panca Sakti University Bekasi (2024). This study aims to improve the speaking skills of seventh-grade students at SMP IT Ummi Abbiyi Serang Baru through a collaborative learning method using the Team-Game-Tournament (TGT) technique. The research employed Classroom Action Research (CAR) with two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through speaking tests, observations, and interviews to assess the accuracy, fluency, and comprehensibility of students' English-speaking abilities. The results indicated a significant improvement in students' speaking skills from the first to the second cycle, with increased active participation and an average score rise from 60% to 74%. Although some students still struggled with fluency and accuracy, most showed progress in understanding the material and speaking with greater confidence. The TGT technique in collaborative learning proved effective in enhancing students' speaking skills, particularly in teamwork, confidence, and comprehension of the material.